Surface and segregation energies of Ag based alloys with Ni, Co and Fe: Direct experimental measurement and DFT study. (15th February 2021) - Zhevnenko, S.N.; Petrov, I.S.; Scheiber, D.; Razumovskiy, V.I.
Abstract: A direct measurement of the surface energy polytherm in Ag + 0.5 at.% Fe alloy and first-principles calculations of segregation energy in silver-based systems with iron, cobalt and nickel were performed. The surface energy was measured in situ on silver foils with 16 μm thickness in the temperature range (0.8 - 0.95) Tm Ag in Ar+10% H2 atmosphere. Iron was introduced by electrolytic deposition and annealing. The segregation energy calculations were performed using density functional theory (DFT). DFT calculations were used to obtain the segregation energies of Fe, Co and Ni on the (100), (110), and (111) surfaces of Ag. It was shown that alloying of silver with Ni, Co and Fe ( 0.5 at.%) leads to a significant increase in the surface energy and this effect increased with decreasing temperature. The alloys behaved in a similar way with decreasing temperature: the surface energy of the alloys increased to values close to the surface energy values of the second components in their standard reference states. DFT calculations of the segregation energy showed a strong "anti-segregation" behavior of Ni, Co and Fe in Ag; the segregation energy took positive values of about 0.4 eV/atom for all solute atoms. Surface studies by AFM and AES methods showed that the surface was two-phase, a silver phase and a small fraction of the second bcc-Fe phase particles coated with a thin silver layer. These observations indicated a quite pronounced desorption of iron on silver on one hand and the adsorption of silver on iron on the other hand. The positive segregation energies of Ni, Co and Fe to Ag surfaces, experimentally observed desorption behavior of these solutes as well as an increase of the surface energy with the increasing concentration of the second component, point at the fundamental reversibility of the Gibbs adsorption equation. Graphical abstract: Image, graphical abstract